Real‐time distortion correction of spiral and echo planar images using the gradient system impulse response function. Issue 6 (26th June 2015) - Campbell‐Washburn, Adrienne E.; Xue, Hui; Lederman, Robert J.; Faranesh, Anthony Z.; Hansen, Michael S.
Abstract : Purpose: MRI‐guided interventions demand high frame rate imaging, making fast imaging techniques such as spiral imaging and echo planar imaging (EPI) appealing. In this study, we implemented a real‐time distortion correction framework to enable the use of these fast acquisitions for interventional MRI. Methods: Distortions caused by gradient waveform inaccuracies were corrected using the gradient impulse response function (GIRF), which was measured by standard equipment and saved as a calibration file on the host computer. This file was used at runtime to calculate the predicted k‐space trajectories for image reconstruction. Additionally, the off‐resonance reconstruction frequency was modified in real time to interactively deblur spiral images. Results: Real‐time distortion correction for arbitrary image orientations was achieved in phantoms and healthy human volunteers. The GIRF‐predicted k‐space trajectories matched measured k‐space trajectories closely for spiral imaging. Spiral and EPI image distortion was visibly improved using the GIRF‐predicted trajectories. The GIRF calibration file showed no systematic drift in 4 months and was demonstrated to correct distortions after 30 min of continuous scanning despite gradient heating. Interactive off‐resonance reconstruction was used to sharpen anatomical boundaries during continuous imaging. Conclusions: This real‐time distortion correction framework will enable the use of these high frame rate imaging methods for MRI‐guided interventions. Magn Reson Med 75:2278–2285, 2016. © 2015 Wiley Periodicals, Inc.